(untitled) (Olhar de Professor, 2023)
This article deals with pedagogical practices of teachers of children aged zero to three years, focusing on care and education actions in the context of daycare. It presents the results of an investigation, completed in 2022, whose problem was to identify which pedagogical practices are developed by teachers of children aged zero to three years in the day-care routine? We sought to identify how and by whom the different and varied activities experienced by children in this age group are developed in a Municipal Early Childhood Education Center (CEI). The methodology consisted of participant observation of the practices developed with children in a public daycare center, located in the city of Campinas/SP, making descriptive records in a field diary, for eight months. At the end, we highlight the clear distinction of tasks between professionals (teachers and monitors) when carrying out activities and which, in our view, also affect children’s learning and development differently. We consider that this distinction causes harm to the quality of adult/child interactions, as the intentionality of each professional’s action is based on different knowledge and educational purposes. Furthermore, the distinction between professionals’ activities can discourage the search for professional improvement, called monitors in this context, who interact with children on a daily basis as much as teachers do.